??? ????? ?????? ?? ????? ??????? ??????? ??????? ????? ????? ?????? ????? ?????? ????? ????????? ?????? - Fitri Rahmadhani Salsabilla (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2020)
In essence, the success of female students in the learning in Gontor not only with intelligence possessed, but there are other factors that will influence this, that factor was the ability to speak Arabic. Arabic language skills is the ability of a person to has the ability to speak include: the ability of hearing, speech, reading, and writing skills are good and right. One of the parties responsible and plays an important role in instilling the ability to speak Arabic in ITTC Darussalam Gontor is master of class, because master of class is as representative headmaster and Director of KMI. Moreover, a new student class 1 KMI much needed next grade level This research is a qualitative descriptive field research, data collection techniques used are: 1) Interview, 2) Observation, and 3) Documentation. And to analyze the data, researchers use Miles and Huberman, namely: 1) Data Reduction, 2) Presentation of Data, and 3) Withdrawal Conclusion and Verivikasi Data. Therefore, the role and efforts master of class 1 in imparting language skills is required. From the analysis conducted, the researcher concludes that: 1) The role of the homeroom teacher in instilling the ability of the language is very important, and the role is: a) Motivate and teach students to be able to have language skills, b) Teaching Arabic with props and requires students to bring dictionary, c) Provide new vocabulary, d) Provide good example, e) Guarding to participate in the following language activities.